Benefits and Costs of Political Connection, Evidence in Indonesia - Lela Nurlaela Wati; Ramdany Ramdany; Momon Momon (Widya Cipta - Jurnal Sekretari dan Manajemen, 2020)
This study aims to analyze the comparison of the quality of financial statements and company attributes (company value, profitability, size, company growth, and leverage) in politically connected and non-politically connected firms. The research sample as many as 871 large companies in Indonesia. By using the independent t-test different test analysis, the results of the study show that the quality of financial statements in politically connected firms is lower than that of politically unconnected firms. However, firm value, profitability, size, company growth, and leverage in politically connected firms are greater than politically unconnected firms. The implications of this study indicate that political connections can provide benefits as well as costs for large companies in Indonesia. Regulators must encourage companies to disclose better information about the company's financial statements. For investors, this result is expected to be an input for determining investment preferences in companies. Future studies are expected to be able to test more comprehensively and compare them with other countries.Keywords: Political Connection, Quality of Financial Statements, Corporate Attributes